Development of a website based on digital learning multimedia for information technology subject in junior high school students - Kesi Kobak; Nurhikmah Nurhikmah; Arnidah Arnidah (Universitas Papua, 2026)
The integration of technology in learning alters teaching methods, fostering a more interactive and collaborative learning environment. Educational multimedia websites improve user interaction, evaluate student comprehension, and provide diverse media. The purpose of this study is to develop a website based on digital learning multimedia in the information technology subject at SMP Pest. Putri Yatama Mandiri Gowa. This research is classified into the category of research and development (R&D). The development model used in this study refers to the ADDIE model. Validation involved media and design experts as well as material experts. The trial involved 10 students in the small-group phase and 30 students in the large-scale trial. The results of the needs analysis showed that several main factors were the basis for development, including the condition of learning facilities that are still limited and the lack of digital media integrated with teaching materials. The results of the validation of the material experts showed that the product was categorized as very valid with a total average of 4.6. Meanwhile, the results of the validation of media and design experts were found to be 4, indicating a valid product. The results of the small-group trial showed an average score of 91.00 in the practical category. The results of the large-scale trial showed an average score of 90.50, indicating the product's effectiveness. The use of a website based on digital learning multimedia has proven to be practical and effective in significantly improving student learning outcomes in the subject of information technology. Therefore, this website based on digital learning multimedia is worthy of being used as an integral part of modern learning strategies, especially in information technology-based learning.